Evolving Era of “Sponges”: Nanosponges as a Versatile Nanocarrier for the Effective Skin Delivery of Drugs - Mullick, Prashansha; R. Hegde, Aswathi; Gopalan, Divya; Pandey, Abhijeet; Nandakumar, Krishnadas; Jain, Sanyog; Kuppusamy, Gowthamarajan; Mutalik, Srinivas (Current Pharmaceutical Design, 2022)
Background: Nanosponge, as a carrier for the skin delivery system for drugs, plays a vital role. It not only serves to administer the drug to the targeted layer of skin but also increases the drug retention and deposition on the skin. Objective: In this review, we aim to highlight the effects of several processes and formulation variables prompting the characteristics of various nanosponges for the delivery of drugs into/ across the skin. Methods: In the present review article, the overall introduction of nanosponges, their preparation, characteristic features, advantages, disadvantages, and factors affecting their preparation, are covered. Furthermore, an elaborative description of nanosponges for skin delivery and its toxicological perspective with some referential examples of nanosponge drugs has also been deliberated here. Results: Factors associated with the formation of nanosponges can directly or indirectly affect its efficacy in the skin delivery of drugs. These nanoforms are efficient in delivering the drugs which possess lower aqueous solubility, therefore, the aqueous solubility of drugs possessing a narrow therapeutic window can easily be enhanced. It also helps in achieving targeted drug delivery, controlled release of drugs, increases bioavailability, reduces drug toxicity, decreases drug degradation, and many more. Conclusion: Nanosponges have been identified as potential drug delivery carriers into as well as across skin. Delivery of biologics such as vaccines, enzymes, peptides, proteins, and antibodies, is also gaining attention in the recent past.
Keywords: skin delivery